From Byron to bin Laden A History of Foreign War Volunteers - Arielli, Nir (Harvard University Press, 2018)
What makes people fight for countries other than their own? Nir Arielli offers a wide-ranging history of foreign-war volunteers, from the French Revolution to Syria. Challenging notions of foreign fighters as a security problem, Arielli explores motivations, ideology, gender, international law, military significance, and the memory of war